PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 028 SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - ', Jumiah; ', Erlisnawati; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract The rescearch is cause is the low social studies students learning outcomes with average grade 62,83. While the udue of minimum criteria of completenes is 65 this researches is classroom action  research (CAR). That suppose to incriasing of the social studies students learning outcomes of fourth grade of elementery school 028 Sintong Tanah Putih in Rokan Hilir district. The formula of the problem is does the aplication of cooperative learning model type two stay two stray (TSTS) can inprove  the social studies studen learning outcomes of fourth grade SDN 028 Sintong Tanah Putih in Rokan Hilir District. Before dairy CAR  the students good average grade 64,48. Ard after CAR the average grade in create is 74,79% whereas on the scord cycle  the average grade increase is 84,79. So the improvement of students learning out comes from the bassed score to cycle I increase about 11,96% whereas from based score to cycle II increase about 10%. The activity of the student in first cycle with an average grade 56,28% and the scord cycle is about 74,99%. The activity of the teacher on the first cycle with an average grade 60,41% and the secord cycle is about 79,16%. The result of this research is the  application of cooperative learning model type Two Stay Two Stray (TSTS) can increase the social studies students learning outcomes at fourth brade of elementary school 028 Sintong Tanah Putih in Rokan Hilir District. Key word : Kooperative type Two Stay Two Stray (TSTS), The social student achievement